Забавная история из жизни животных как рече- вой жанр интернет-коммуникации - Хорохордина , Ольга; Zheng, Xiaotang (Acta Polono-Ruthenica, 2021)
The authors of the article analyze selected texts of Internet communication, identify the speech genre of a funny story from the life of animals, identify its typological parameters in accordance with a concept developed by Mikhail Bakhtin, show the stylistic originality of the ironically written and spoken presentation of the plot, compare the specified genre of Internet communication with the related non-media genre of funny stories, and demonstrate the similarities and differences between the compared genres. The authors note that the genre of a funny story from the life of animals reveals its belonging to the Internet communication environment with such properties as the attractiveness of the emotiogenic situation underlying its plot, hypertextual connection within the frame of entertainment sites, forums, and channels of the source text with other narrative texts of the same genre as well as with reactive replicas-comments, where an abbreviated version of this genre is implemented and from whose totality a polylogue is formed as a reflection of the interactivity of Internet communication. The authors state the kinship of the compared genres and pay attention to the prospects of studying the specifics of Internet genres against the background of their non-media counterparts. The research material consists of 40 Internet texts.